Trustworthy component model supporting networks reconfiguration - Bo YUAN; Bin-qiang WANG; Dong-chao MA (Tongxin xuebao)
Based on principles of the separation of concerns and the dynamic software architecture (DSA) technology, a component model named TCM(trustworthy component model)was proposed. Formation and assemblage of components were analyzed, then a trustworthy data security sealing mechanism was proposed. By sealed the data, the TCM not only support reconfiguring components, but also prevent component hostility operation, which can destroy the data transmis-sion. A container prototype was implemented, and experimental applications were implemented to validate this approach. The results show that this model can change the topology of components and find out the hostility components, which improve the trustworthy of reconfigurable flexible network node.